Semantic prosody [ a critical evaluation - Stewart, Dominic (Routledge advances in corpus linguistics, 2010)
Presents a full-length treatment of semantic prosody, a concept akin to connotation but which connects crucially with typical lexical environment. This work discusses the relevance of the theory of priming in this area, and whether semantic prosody has cogency as a theoretical concept